2011
DOI: 10.1260/2040-2295.2.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Capsule Endoscopy: Opportunities and Challenges

Abstract: The increasing demand for non-invasive (or less-invasive) monitoring and treatment of medical conditions has attracted both physicians and engineers to work together and investigate new methodologies. Wireless capsule endoscopy is a successful example of such techniques which has become an accepted routine for diagnostic inspection of the gastrointestinal tract. This method offers a non-invasive alternative to traditional endoscopy and provides the opportunity for exploring distal areas of the small intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It usually deploys leg-like mechanisms [ 32 , 33 , 34 , 40 , 50 , 55 ] or uses a magnetic field [ 56 , 57 ] to attach the capsule to the inner wall of the GI tract. The release mechanism is triggered to deliver drugs in a controlled manner and involves a reservoir [ 12 , 40 , 58 ] with release triggered by specific environmental conditions, e.g., temperature or pH [ 50 ], or by activation of a magnetic field [ 56 ].…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…It usually deploys leg-like mechanisms [ 32 , 33 , 34 , 40 , 50 , 55 ] or uses a magnetic field [ 56 , 57 ] to attach the capsule to the inner wall of the GI tract. The release mechanism is triggered to deliver drugs in a controlled manner and involves a reservoir [ 12 , 40 , 58 ] with release triggered by specific environmental conditions, e.g., temperature or pH [ 50 ], or by activation of a magnetic field [ 56 ].…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…The VECTOR Project (supported by the European Union) revealed that the peak power required will be at least few hundred mW after taking into consideration all the on board power-consuming modules within a RCE [30,31]. Moreover, some advanced features including microsurgery, drug delivery and biopsy are also anticipated for multifunctional medical robot (MMR) WCE [32,33] that will also increase the power demands of the new generation of WCE systems. Accordingly, it can be concluded that the peak power requirement for the new generation of WCE is becoming much higher than that of the existing WCE units and the battery capacity may not be sufficient [30,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…[188][189][190] Various commercial prototypes of capsule endoscope such as IntelliCap, [191,192] InteliSite, [193] Pulsincap, [194] and Enterion capsule, [195] have been designed and fabricated to achieve triggered drug release via different mechanisms. [188][189][190] Various commercial prototypes of capsule endoscope such as IntelliCap, [191,192] InteliSite, [193] Pulsincap, [194] and Enterion capsule, [195] have been designed and fabricated to achieve triggered drug release via different mechanisms.…”
Section: Wireless Endoscopic Capsulesmentioning
confidence: 99%